Zum Einsatz von authentischen Texten im Fremdsprachenunterricht im Hinblick auf die Anforderungen des Arbeitsmarktes am Beispiel des Projekts/Lehrwerks: Wirtschaftsdeutsch als Fremdsprache. Ein Leitfaden mit ausgewählten Themen für die Praxis - Kujawa, Izabela (2022)
The topic of the article is the selection of authentic texts and their use during ' Business German' course. It has been explained what an authentic text is and what is the role of authentic texts in the context of foreign language teaching. The coursebook ' Business language as a foreign language. The guide with chosen topics for practical use’ has been presented as a source of didactic materials comprising authentic texts selected with the consideration of the labour market.
Keywords: authentic texts in foreign language didactics; foreign language teaching with consideration of labour market; language for specialist purposes; Business German